High-efficiency bubble transportation in an aqueous environment on a serial wedge-shaped wettability pattern. Issue 22 (21st May 2019) - Song, Jinlong; Liu, Ziai; Wang, Xuyue; Liu, Hong; Lu, Yao; Deng, Xu; Carmalt, Claire J.; Parkin, Ivan P.
Abstract : A serial wedge-shaped wettability pattern is designed to achieve long-distance spontaneous and directional pumpless transportation of subaqueous gas bubbles. Abstract : Spontaneous and directional pumpless transportation (SDPT) of subaqueous gas bubbles has great prospects in eliminating destructive gas bubbles in fluid transportation pipes. However, with current technology it is difficult to realize non-buoyancy driven long-distance SDPT. How to realize long-distance SDPT of subaqueous gas bubbles and how to fabricate a surface with the capacity of long-distance SDPT of subaqueous gas bubbles on engineering metals still remain a challenge. Here, a serial wedge-shaped wettability pattern with an exterior surrounding subaqueous superaerophobic region and interior subaqueous superaerophilic region is designed to realize long-distance SDPT of subaqueous gas bubbles. The process is driven by unbalanced surface tension forces; hence, subaqueous gas bubbles can not only be transported on a horizontal and straight pattern, but can also be easily transported on a horizontal and spiral-shaped pattern or on a wave-shaped pattern that is spatially tilted. In addition, a universal method composed of electrochemical etching and laser etching is also proposed to fabricate the serial wedge-shaped wettability pattern on various engineering metal materials including Al, Mg alloy, Ti alloy, and Zn.